2016
DOI: 10.1016/j.mri.2016.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Gadolinium toxicity and treatment

Abstract: a b s t r a c t a r t i c l e i n f oGadolinium based contrast agents (GBCAs) play an important role in the diagnostic evaluation of many patients. The safety of these agents has been once again questioned after gadolinium deposits were observed and measured in brain and bone of patients with normal renal function. This retention of gadolinium in the human body has been termed "gadolinium storage condition". The long-term and cumulative effects of retained gadolinium in the brain and elsewhere are not as yet u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
57
1
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(69 citation statements)
references
References 51 publications
1
57
1
3
Order By: Relevance
“…The r 1 (brightening) relaxivity value of the complexes are in the range of 3.0–5.0 m m –1 s –1 at 1.5 T, 298 K. Because of the low r 1 values, administration of a large dose (0.05–0.10 m m kg –1 ) of contrast agent is required . Recent investigation on the adverse effect of Gd III ‐contrast agents revealed that the accumulation of Gd III ions in human body causes fatal diseases, for example Nephrogenic systemic fibrosis (NSF), Gadolinium deposition disease (GDD) etc . Hence, the reduction of the quantity of the dose is essential.…”
Section: Introductionmentioning
confidence: 99%
“…The r 1 (brightening) relaxivity value of the complexes are in the range of 3.0–5.0 m m –1 s –1 at 1.5 T, 298 K. Because of the low r 1 values, administration of a large dose (0.05–0.10 m m kg –1 ) of contrast agent is required . Recent investigation on the adverse effect of Gd III ‐contrast agents revealed that the accumulation of Gd III ions in human body causes fatal diseases, for example Nephrogenic systemic fibrosis (NSF), Gadolinium deposition disease (GDD) etc . Hence, the reduction of the quantity of the dose is essential.…”
Section: Introductionmentioning
confidence: 99%
“…This feature is important in patients with renal failure but is generally beneficial regarding recent reports on gadolinium deposition in the brain. 38 In our patients, with, at most, mild cognitive impairments, the additional imaging time of approximately 10 -15 minutes was well-tolerated; however, longer scan times may be a problem in severely debilitated patients with major stroke. Superselective pCASL enables perfusion readout throughout the brain with accurate anatomic reference as an overlay.…”
Section: Discussionmentioning
confidence: 68%
“…They are usually cleared from the blood in about 1.5 hours, and completely recovered from the urine in 7 days (.90% in the first 12 hours). [48][49][50] However, the concentrations used in this study are far less than the concentrations which could be toxic. Growing evidence supports the hypothesis that Gd-containing contrast agents (0.05-0.2 mmol/kg) used for MRI could trigger the development of nephrogenic systemic fibrosis (NSF).…”
Section: Discussionmentioning
confidence: 98%
“…17 Gadolinium (Gd), an element of lanthanide, has been widely used as a contrast agent for magnetic resonance imaging (MRI) studies. 18 Many studies have shown a considerably higher level of Gd deposition in bone tissue, indicating that bone might be a preferential site of Gd deposition. [19][20][21][22] Thus, Gd-containing biomaterials have attracted considerable interest worldwide.…”
Section: Introductionmentioning
confidence: 99%